Pengaruh E-Promotion, E-Wom dan Lokasi Terhadap Kepuasan Konsumen Melalui Keputusan Pembelian sebagai Variabel Intervening pada Toko Elektronik Lubuklinggau - Bujang Putri; Ronal Aprianto; Apandi Apandi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the effect of e-Promotion, e-WOM, and location on consumer satisfaction through purchasing decisions as an intervening variable in Lubuklinggau electronics stores. The research design used an associative approach, where the study was conducted to determine the influence, relationships, and to test hypotheses. The population and sample in this study were 165 people. Data analysis used t-tests and F-tests. The results showed that 1) There is an effect of e-Promotion on consumer satisfaction in Lubuklinggau electronics stores, with t-test (2.292) < t-table (1.697). 2) There is an effect of e-WOM on consumer satisfaction in Lubuklinggau electronics stores, with t-test (2.292) < t-table (1.697). 3) There is an effect of location on consumer satisfaction in Lubuklinggau electronics stores, with t-test (1.598) > t-table (1.697). 4) There is an influence of E-Promotion on Consumer Satisfaction through Purchasing Decisions as an Intervening Variable in Lubuklinggau Electronics Stores, namely F count (5.849) > F table (4.17). 5) There is an influence of E-Wom on Consumer Satisfaction through Purchasing Decisions as an Intervening Variable in Lubuklinggau Electronics Stores, namely F count (5.849) > F table (4.17). 6) There is an influence of Location on Consumer Satisfaction through Purchasing Decisions as an Intervening Variable in Lubuklinggau Electronics Stores, namely F count (5.849) > F table (4.17).